2020
DOI: 10.1038/s41598-020-66812-1
|View full text |Cite
|
Sign up to set email alerts
|

Wheat growth, applied water use efficiency and flag leaf metabolome under continuous and pulsed deficit irrigation

Abstract: The intensity and frequency of precipitation events are predicted to change over the coming decades. For many areas, longer periods without rainfall are expected. We investigated the importance of irrigation frequency under water deficit conditions for growth, physiology and chemistry of wheat (Triticum aestivum). Drought-stressed plants received 40% of the water provided for control plants and were either watered every other day (continuous drought, cd) or every eight days (pulsed drought, pd). Maximum quantu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 65 publications
6
25
1
Order By: Relevance
“…In this study, 125 biologically active compounds of a phenolic and nonphenolic nature were identified in differently pigmented wheat grains by HPLC coupled with Bruker Daltonics ion trap MS/MS (Table 1). Our annotation results are consistent with the extensive mass-spectrometric literature data on the wheat T. aestivum [27][28][29][30][31][32][33] and other plant matrices, e.g., Passiflora incarnate [34], Bituminaria [35], Phyllostachys nigra [36], Carpobrotus edulis [37], and Vaccinium macrocarpon [38]. For example, the collision-induced dissociation spectrum (in negative ion mode) of a flavone called apigenin 2 -O-sinapoyl, C-hexosyl, C-pentosyl from extracts of T. aestivum grains [line S29 BLUE (4Th-4D)] is given in Figure 7.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, 125 biologically active compounds of a phenolic and nonphenolic nature were identified in differently pigmented wheat grains by HPLC coupled with Bruker Daltonics ion trap MS/MS (Table 1). Our annotation results are consistent with the extensive mass-spectrometric literature data on the wheat T. aestivum [27][28][29][30][31][32][33] and other plant matrices, e.g., Passiflora incarnate [34], Bituminaria [35], Phyllostachys nigra [36], Carpobrotus edulis [37], and Vaccinium macrocarpon [38]. For example, the collision-induced dissociation spectrum (in negative ion mode) of a flavone called apigenin 2 -O-sinapoyl, C-hexosyl, C-pentosyl from extracts of T. aestivum grains [line S29 BLUE (4Th-4D)] is given in Figure 7.…”
Section: Discussionsupporting
confidence: 90%
“…To maintain the turgor, osmolytes such as sugars and amino acids, in particular proline, are accumulated in plant cells (Singh, Kumar, Singh, Singh, & Prasad, 2015; Tatar & Gevrek, 2008). In flag leaves of wheat, various metabolites respond in distinct directions to different drought scenarios (Stallmann, Schweiger, Pons, & Müller, 2020). These changes emphasize that drought also has an impact on plant chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…This herbivore proliferates particularly on the inflorescences and can cause severe yield losses by impacting grain filling and by transmitting plant viruses [ 30 ]. In a previous publication, we demonstrated that the biomass of wheat plants was lower for drought-exposed plants than for well-watered plants, indicating that drought caused some stress, whereas the applied water use efficiency was higher in drought-stressed plants [ 31 ]. Furthermore, the metabolome of wheat flag leaves differed between drought-exposed and well-watered plants, measured at two different time points [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous publication, we demonstrated that the biomass of wheat plants was lower for drought-exposed plants than for well-watered plants, indicating that drought caused some stress, whereas the applied water use efficiency was higher in drought-stressed plants [ 31 ]. Furthermore, the metabolome of wheat flag leaves differed between drought-exposed and well-watered plants, measured at two different time points [ 31 ]. Changes in the leaf metabolome were more pronounced in plants exposed to pulsed drought stress compared to continuously drought-stressed plants, although all drought-stressed plants received the same cumulative amount of water [ 31 ].…”
Section: Introductionmentioning
confidence: 99%